Teacher’s Perspective on the Use of ICT in the Classroom: Teacher Elementary School Context - Wahyu Permata, Indah; Purnawarman, Pupung (Institut Agama Islam Negeri Parepare, 2024)
This study investigates the perspectives and incentives of elementary school educators interested in integrating ICT-based learning resources into their teaching methods. The study followed a quantitative approach using surveys, interviews, and observations to gather data, using questionnaires and interviews as data collection tools. The results indicate that most teachers exhibit a positive attitude towards employing ICT in their teaching, with quantitative analysis often categorizing elementary school educators according to their use of learning media. However, the implementation of ICT-based resources is not without its challenges. In conclusion, this study underscores the need for pedagogical adjustments, emphasizing educators' need to continually enhance their ICT knowledge and teaching strategies through training, whether offered by educational institutions or external organizations. This will enable teachers to adapt and refine their teaching methods effectively.